Entrepreneurial behavioral characteristics: a study with academics of administration of a brazilian university - Minello, Italo Fernando; Bürger, Rafaela Escobar; Krüger, Cristiane (Revista de Administração da UFSM, 2017)
With the purpose of exploring the panorama of academic entrepreneurship, it was proposed to carry out this study, which aims to analyze the entrepreneurial behavioral characteristics (CCE’s) in undergraduate students in the administration of a higher education institution. For this, the following specific objectives were established: to outline the profile of the management students of the studied institution; Mapping the entrepreneurial behavioral characteristics of these academics; And propose actions to improve these characteristics. The research, with a quantitative and descriptive methodological approach, obtained a sample of 374 students responding to the McClelland CCE’S questionnaire, allowing the identification of deficiencies in the characteristics “persistence”, “taking calculated risks”, “goal setting” and “persuasion and networks Of contact”. Thus, it is suggested that the governing bodies of this university encourage the creation of programs and projects that stimulate the development of the entrepreneurial behavior of its students, in view of the relevance of the entrepreneur's role in society.